Evaluation methods and characterization of odor pollution from typical waste disposal facilities: a review - WU Chuan-dong; LIU Jie-min; LIU Shi-hua; YAN Lu-chun; ZHAO Peng; SHU Mu-shui (工程科学学报, 2017)
Odor pollution from typical sources has drawn enormous attention because of its strong irritation potential and wideranging and harmful effects to nearby residents. Substantial studies on evaluation methods and characterization of such odor pollution have been conducted all over the world. Advancements in sampling and analysis, prediction methods, and the characterization of odor pollution have taken place in recent years. In this study, specific literature was reviewed on evaluation and prediction methods, characterization, and control strategies for odor pollution from typical waste disposal facilities.